Mapping Badminton Research Scopus Database: A Bibliometric Analysis - Khaeroni Khaeroni; Yasep Setiakarnawijaya; Karisdha Pradityana (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to answer the research questions) how is the development of publications about badminton? 2) What publication themes are related to badminton? 3) What publication opportunities can be done in the future? Â . Article should be started by Title of Article followed by Authors Name and Affiliation Address This research uses the Scopus database which is retrieved using the publish or perish application. From the results of data extraction, 142 articles were obtained with keywords in the badminton article title. This research uses keyword co-occurrence analysis to identify and explore the main fields and topics that appear in publications. The application used to analyse the data is VosViewer. Based on the results of VosViewer analysis, there are eight clusters, with research trends increasing every year. With bibliometric analysis, it is expected to be a reference for researchers, especially about badminton, to continue to develop knowledge.